51 - CHARACTERIZATION OF SCIENTIFIC LITERATURE ON WORK ACCIDENTS INVOLVING BIOLOGICAL MATERIAL (Fiep Bulletin - online, 2011)
Introduction: during patient care, the Health workers are exposed to numerous occupational hazards caused by chemical factors, physical, mechanical, biological, ergonomic and psychosocial problems that can lead to accidents at work. Among a myriad of risks, the biological pose a major threat to occupational health care. Objective: to characterize the scientific productivity on accidents with biological materials, regarding the thematic studies, subject research, type material agent that caused the accident, occupational category most affected, place where most accidents happen and the notification of this accident. Materials And Methods: It is a survey of the literature undertaken using online scientific articles available on the Virtual Health Library (BVS), specifically in the databases of Latin American Literature (LILACS), Brazilian literature of dentistry (BBO) and the database of Nursing (BDENF). Results And Discussion: the most cited issue was about the occurrence of accidents at work related to biological material exposure, six articles was carried out with all health professionals. Concerning to the type material agent that caused injury, 80% were by needles, and the nursing auxiliaries are the main victims. With regard to the place where this kind of accident happens were hospitals. With respect to notification of accidents, we identified the lack of trained professionals to the events, often leading to sub notification. General Discussion: this article adds a better understanding on occupational accidents involving health care staff exposed to biological material so that preventive measures are outlined to minimize them and reduce sub notification.
Keywords: Accidents at work; Accidents; Biological events